2020
DOI: 10.1111/jdv.16803
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent use of biologic agents for the treatment of psoriasis in adults

Abstract: Current clinical recommendations suggest that continuous treatment of moderate‐to‐severe psoriasis with biologic agents is more effective than intermittent treatment in terms of achieving remission and maintaining it. Intermittent treatment, however, may provide an alternative approach in patients unwilling or unable to maintain a continuous regimen, such as those who would prefer a ‘treatment vacation’ after achieving long‐term remission, those who require treatment cessation owing to adverse events, and wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…One aspect of dose adjustment that was not considered in this review is intermittent dosing, although a small number of studies included interrupted dosing within the definition of dose reduction. A recent review identified 18 reports of intermittent use of biologic therapies and concluded that the majority of patients (≥ 60%) were generally able to re-establish disease control following re-treatment and that safety profiles were similar with intermittent and continuous dosing [ 30 ]. However, an earlier systematic review reported that withdrawal of treatment typically led to an increase in disease activity, and retreatment did not result in equivalent response rates to initial therapy for most biologics [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of dose adjustment that was not considered in this review is intermittent dosing, although a small number of studies included interrupted dosing within the definition of dose reduction. A recent review identified 18 reports of intermittent use of biologic therapies and concluded that the majority of patients (≥ 60%) were generally able to re-establish disease control following re-treatment and that safety profiles were similar with intermittent and continuous dosing [ 30 ]. However, an earlier systematic review reported that withdrawal of treatment typically led to an increase in disease activity, and retreatment did not result in equivalent response rates to initial therapy for most biologics [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection was treated with antifungal drug without discontinuing secukinumab. In such a condition, “intermittent treatment” may provide an alternative approach for patients whose treatment require cessation because of adverse events 37 …”
Section: Discussionmentioning
confidence: 99%
“…111,112 Similar to IL-17 inhibitors, IL-23 inhibitors have lower immunogenicity than TNF-inhibitors, and the reproducible effect can be observed on cases that had once achieved treatment success. 88,113…”
Section: Il-12/23 P40 Il-23 P19 and The Inhibitorsmentioning
confidence: 99%
“…IL‐17A is involved in the progression of atherosclerosis, 80 liver cirrhosis, 81‐83 and the mechanism of insulin resistance 84 . Generally, IL‐17 inhibitors have lower immunogenicity than that of TNF inhibitors, and the re‐initiation of IL‐17 inhibitor therapy shows a reproducible effect in cases that had once achieved treatment success 85‐88 …”
Section: Cytokine‐targeted Therapiesmentioning
confidence: 99%